The Impact of the Characteristics of Enterprise Resource Planning (ERP) Systems in Improving the Quality of Accounting Information in Telecom Companies in the Republic of Yemen: A Field Study - Al-Sorihi, Sultan Ali Ahmed; Kolaib, Wala Gamal Ahmed (University of Science and Technology Journal for Management and Human Sciences, 2025)
The study aimed to measure the impact of the characteristics of enterprise resource planning (ERP) systems in improving the quality of accounting information in telecommunications companies in the Republic of Yemen. To achieve the goal of this study, the questionnaire was relied upon as a tool for collecting data, from the population represented by 609 members, from which a stratified random sample of size was taken. It reached 248 accountants, financial management and its various departments, database managers, programmers, and engineers working on ERP systems in telecommunications companies. To analyze the data, through which simple regression analysis was used to test the main hypothesis of the study, and multiple regression to test the sub-hypotheses. The results of the field study showed a positive effect of the characteristics of ERP systems: (technical, organizational, and informational) in improving the quality of accounting information. Based on multiple regression analysis, the results showed that organizational characteristics have a high positive impact on improving the quality of accounting information, followed by technical characteristics, then informational characteristics. In light of the results reached, the study recommended the need to enhance interest by Yemeni telecommunications companies in the ERP system in all its dimensions, and working to continuously improve it to suit the needs of companies because it has an effective role in improving the quality of accounting information. It also recommended working to exert more effort and follow up on all developments related to the ERP system by adopting all new in the field of information and communications technology due to the global trend based on knowledge and innovation.